2021
DOI: 10.3892/ol.2021.12725
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long‑noncoding RNA PTPRG‑AS1 can predict the poor prognosis and promote migration and invasion in patients with osteosarcoma

Abstract: The present study aimed to determine the expression of the long non-coding RNA PTPRG-AS1 in patients with osteosarcoma, and to explore its role on the prognosis of patients and the process of osteosarcoma cell metastasis. Reverse transcription quantitative-PCR was performed to detect PTPRG-AS1 expression in osteosarcoma tumor tissues and cells (U2OS, SJSA1 and Saos-2), and normal tissues and cells (hFOB1.19). In addition, qPCR and western blotting were also used to detect mRNA and protein expression, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The first hematological malignancy where a key role of PTPRG was discovered is the Ph + chronic myeloid leukemia (CML). Della Brest, Bone, others Alteration (Zhao et al, 2014;Iranpour et al, 2016;Ge et al, 2021) Peruta et al reported how the tyrosine phosphorylation of BCR-ABL1, CRKL and STAT5 were decreased in PTPRG-transfected K562 and reported downregulation of PTPRG mRNA and protein in CML patients (Della Peruta et al, 2010). This type of result was independently replicated confirming the inhibitory activity of PTPRG on BCR-ABL1 protein and on substrates influenced by itself such as ERK1/2 kinase (Drube et al, 2018).…”
Section: Ptprg Interacts With Characteristic Oncogenes In Specific Cancer Types Leukemia and Lymphomasmentioning
confidence: 84%
See 3 more Smart Citations
“…The first hematological malignancy where a key role of PTPRG was discovered is the Ph + chronic myeloid leukemia (CML). Della Brest, Bone, others Alteration (Zhao et al, 2014;Iranpour et al, 2016;Ge et al, 2021) Peruta et al reported how the tyrosine phosphorylation of BCR-ABL1, CRKL and STAT5 were decreased in PTPRG-transfected K562 and reported downregulation of PTPRG mRNA and protein in CML patients (Della Peruta et al, 2010). This type of result was independently replicated confirming the inhibitory activity of PTPRG on BCR-ABL1 protein and on substrates influenced by itself such as ERK1/2 kinase (Drube et al, 2018).…”
Section: Ptprg Interacts With Characteristic Oncogenes In Specific Cancer Types Leukemia and Lymphomasmentioning
confidence: 84%
“…Furthermore, with the advent of genomic technologies we have begun to understand additional post-translational regulatory mechanisms imposed by ncRNAs, such as miRNA and lncRNA. Surprisingly, the antisense RNA 1 of PTPRG (PTPRG-AS1) was found to be upregulated in different solid cancers representing a significant emerging predictor for tumor progression ( Faghihi and Wahlestedt, 2009 ; Wang and Chang, 2011 ; Ge et al, 2021 ). Despite the fact that it has been clarified a suppressive role for PTPRG in various tumors, limited data suggesting an oncogenic role by the receptors PTPRZ/PTPRG in glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that the lncRNAs, MIAT [ 42 ], GABPB1 [ 43 ], and PDPK2P [ 44 ] influence tumor progression in HCC. Additionally, research revealed a relationship between PTPRG-AS1 and epithelial ovarian cancer [ 27 ] or osteosarcoma [ 45 ]. However, whether PTPRG-AS1 participates in the tumor progression of HCC has not been investigated.…”
Section: Discussionmentioning
confidence: 99%